2011
DOI: 10.1016/j.nuclphysb.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

A universal lower bound on the specific temperatures of AdS-Reissner–Nordström black holes with flat event horizons

Abstract: We show that, in a gravitational theory [in any number of dimensions greater than 3] which admits BPS branes and AdS-Reissner-Nordström black holes with flat event horizons, the specific [dimensionless] temperature of such a black hole is bounded below by ≈ 0.156875. This confirms the recent suggestion by Hartnoll and Tavanfar, to the effect that no such black hole can be arbitrarily cold, since from the AdS/CFT dual point of view the low-temperature degrees of freedom should not be concealed by the equivalent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
2
8
0
Order By: Relevance
“…(3.10) the mass of flat uncharged black hole is, with our normalization condition, M = 3π 2 K 3 /2. For consistency check, we note that the flat uncharged black hole has metric [21] Thus with our normalization condition, and L = 1, we get indeed Eq. (5.16).…”
Section: Robustness Of Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…(3.10) the mass of flat uncharged black hole is, with our normalization condition, M = 3π 2 K 3 /2. For consistency check, we note that the flat uncharged black hole has metric [21] Thus with our normalization condition, and L = 1, we get indeed Eq. (5.16).…”
Section: Robustness Of Resultssupporting
confidence: 52%
“…Embedding the black hole into string theory however, exposes it to the menace of Seiberg-Witten instability [18,19], which is induced by uncontrolled brane pair production, analogous to the Schwinger mechanism of vacuum polarization [20]. Indeed, it has been shown that Reissner-Nordström black holes do "universally" become unstable in the Seiberg-Witten sense for all spacetime dimensions above 3 [21]. It is therefore interesting to study whether charged dilaton black holes are also vulnerable to Seiberg-Witten instability.…”
Section: Introductionmentioning
confidence: 99%
“…Seiberg and Witten stressed that the situation is particularly delicate when the boundary geometry is [scalar-]flat -which is precisely the case here. In [65] [85] it was shown that electrically neutral AdS black holes with flat event horizons are stable in this sense, and in fact this remains true for most values of the electric charge below the extremal value. However, when the electric charge becomes sufficiently large but still sub-extremal, the distortion of the branes does become large enough to trigger the instability.…”
Section: Fatal Attraction Toward Extremalitymentioning
confidence: 98%
“…It turns out that the addition of small amounts of electric charge to a black hole with a flat event horizon has no ill-effects, that is, the brane action remains positive everywhere. But [for four-dimensional black holes] when the charge reaches about 92% of the extremal charge [85] -that is, when the temperature is low, but not zero -the brane action becomes negative at a certain distance from the black hole, triggering a pair-production instability. In short, we have exactly what we need, supplied by basic objects in string theory.…”
Section: Quark Gluon Plasma [Qgp]mentioning
confidence: 99%
See 1 more Smart Citation